The Future Security Environment in the Middle East Conflict, Stability, and Political Change - Bensahel, Nora (RAND Corporation, 2004)
This report identifies several important trends that are shaping regional security. It examines traditional security concerns, such as energy security and the proliferation of weapons of mass destruction, as well as newer challenges posed by political reform, economic reform, civil-military relations, leadership change, and the information revolution. The report concludes by identifying the implications of these trends for U.S. foreign policy.